“Analisis Makna Semantik Pada Puisi Chairil Anwar DOA” - Putri Firmawindy Turnip; Alzyra Fatihah Simatupang; Elsah Sinurat; Yuliana Sari (Simpati, 2024)
This study analyzes the semantic meaning in the poem "DOA" by Chairil Anwar. The poem was chosen for its richness of language and depth of meaning. Through a semantic approach, this research aims to explore the meaning of key words in the poem and how these words contribute to the overall construction of meaning. The analytical method involves searching for both denotative and connotative meanings of each word, as well as understanding the cultural and historical context in which the poem was created. Findings from this analysis provide profound insights into the thoughts and feelings conveyed by Chairil Anwar through the poem "DOA."